Performance evaluation of proposed asymmetric turbo code in WCDMA HSDPA system - Ramasamy, K.; Balamuralithara, B.; Siddiqi, Mohammad Umar (2009)
This paper considers the application of the proposed asymmetric turbo code system in MIMO High Speed Downlink Packet Access (HSDPA) service of WCDMA. In typical turbo code system, an encoder with code rate 1/3 is used together with bit repetition to achieve the code rate 1/4. However, this approach suffers from weak Bit Error Rate (BER) performance compared to the more complex encoding system which implements puncturing scheme in order to achieve code rate 1/4. In this paper, we used the proposed asymmetric turbo code system to mitigate the weak BER performance introduced in bit repetition scheme. At the same time, we found that the proposed asymmetric turbo code system could achieve high throughput compared to typical turbo code system used in HSDPA system. The performance of typical turbo code and proposed asymmetric turbo code using bit repetition and puncturing schemes is studied in MIMO HSDPA system using MATLAB simulation and compared. From the simulation results, it is observed that the proposed asymmetric turbo code system performs better and it provides coding gain of 0.2dB to 0.3dB and the total throughput is also increased up to 10% compared to typical turbo code system in MIMO HSDPA.